2012
DOI: 10.2169/internalmedicine.51.6846
|View full text |Cite
|
Sign up to set email alerts
|

Familial Mediterranean Fever with Onset at 66 Years of Age

Abstract: The patient was a 68-year-old woman who had experienced recurrent febrile episodes since 66 years of age. Despite various examinations and treatments, the etiology remained unclear. Further examinations following another referral failed to uncover the cause. Therefore, despite her age, it was presumed that she had familial Mediterranean fever. An analysis of the familial Mediterranean fever (MEFV) gene detected heterozygous L110P, E148Q, and R202Q mutations. No further febrile episodes occurred after colchicin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…Based on a nationwide survey of FMF in Japan, the mean age of onset is 19.6 ± 15.9 years and in only 6% of all reported cases did onset occur after 50 years of age . Onset in patients in their 50s and 60s has also been reported, but to the best of our knowledge, there has been no report of any patient with onset in his or her 70s, even in Japan.…”
Section: Discussionmentioning
confidence: 96%
“…Based on a nationwide survey of FMF in Japan, the mean age of onset is 19.6 ± 15.9 years and in only 6% of all reported cases did onset occur after 50 years of age . Onset in patients in their 50s and 60s has also been reported, but to the best of our knowledge, there has been no report of any patient with onset in his or her 70s, even in Japan.…”
Section: Discussionmentioning
confidence: 96%
“…Inoue et al recently reported the case of an FMF patient with onset at 66 years of age (5), and Mori et al reported an FMF patient with onset at 60 years of age (6). To the best of our knowledge, two of the present cases are the oldest reported FMF patients in Japan (5)(6)(7)(8). According to the nationwide study of FMF in Japan, the mean age at the time of diagnosis was 28.7±18.5 years, and the mean age at the onset of symptoms was 19.6±15.3 years (2).…”
Section: Discussionmentioning
confidence: 60%
“…10 Additionally, the patient had repeated febrile attacks that occurred 10 times a month. The onset of FMF is usually before 20 years of age and the intervals between attacks are irregular, ranging from 1 week to several years.…”
Section: Discussionmentioning
confidence: 99%
“…This is the second oldest onset of FMF reported following a case with an onset age of 66 years. 10 Additionally, the patient had repeated febrile attacks that occurred 10 times a month. This is the most frequent typical attack rate ever reported.…”
Section: Discussionmentioning
confidence: 99%